The pathophysiologic and prognostic significance of acidosis in severe adult malaria. - Day, N; Phu, N; Mai, N; Chau, T; Loc, P; Chuong, L; Sinh, D; Holloway, P; Hien, T; White, N (2000)
OBJECTIVE: To investigate the pathophysiology and prognostic significance of acidosis in severe adult malaria. DESIGN: Cohort study. SETTING: The intensive care unit of an infectious diseases hospital in southern Vietnam. PATIENTS: Three hundred forty-six consecutive adult patients with severe falciparum malaria. INTERVENTIONS: Measurements of baseline venous lactate and pyruvate concentrations and an extensive range of clinical and laboratory variables were made, and patients were followed up carefully until death or discharge from the hospital. Admission arterial blood pH and gas tensions were recorded in 296 patients, and hepatic venous sampling was done in 12 patients. MEASUREMENTS AND MAIN RESULTS: Overall, 198 (67%) patients were acidotic (standard base deficit [SBD], >3.3 mmol/L [n = 196], or arterial Pco2, >45 torr [6 kPa] [n = 3]). Hyperlactatemia (plasma lactate, >4 mmol/L) occurred in 120 (35%) of the 346 patients and was associated significantly with acidosis (p < .0001). The hepatosplanchnic lactate extraction ratio was negatively correlated with mixed venous plasma lactate (r2 = .50; p = .006). Hyperlactatemia, metabolic acidosis (SBD, >3.3), and acidemia (pH <7.35) were strongly positively associated with a fatal outcome (relative risks [95% confidence interval], 4.3 [range, 1.8-10.6], 5.0 [range, 3.0-8.1], and 2.7 [range, 1.8-4.1], respectively). The SBD was the single best clinical or laboratory predictor of fatal outcome. The overall median lactate/pyruvate ratio was raised at 30.6 (range, 20.6-62.3; normal range, <15), suggesting hypoxia and anaerobic glycolysis, and was significantly higher in fatal cases (p < .0001). In an additive multivariate model, the two main independent contributors to metabolic acidosis were plasma creatinine, as a measure of renal dysfunction, and venous plasma lactate, together accounting for 63% of the variance in SBD. In univariate analyses, they contributed 29% and 38%, respectively. CONCLUSIONS: These results confirm the importance of acidosis in the pathophysiology of severe adult malaria and suggest a multifactorial origin involving tissue hypoxia, liver dysfunction, and impaired renal handling of bicarbonate.